Defense Resource Planning Under Uncertainty An Application of Robust Decision Making to Munitions Mix Planning - Lempert, Robert J. (RAND Corporation, 2016)
Defense planning faces significant uncertainties. This report applies robust decision making (RDM) to the air-delivered munitions mix challenge. RDM is quantitative, decision support methodology designed to inform decisions under conditions of deep uncertainty and complexity. This proof-of-concept demonstration suggests that RDM could help defense planners make plans more robust to a wide range of hard-to-predict futures.